Pengalaman Kehilangan Keperawanan (Virginitas) pada Mahasiswi di Institusi X: Study Fenomenology - Eli Kurniasih; Chita Widia; Soni Hersoni (Jurnal Keperawatan Galuh, 2025)
The concept of virginity, shaped by social, cultural, and religious factors, often leads to gender inequality that disadvantages women. This study aims to describe the experience of losing virginity among female health students, including the timing, causes, and impacts. The study involved seven active female students selected using the snowball sampling method with a purposive technique. Data were collected through in-depth interviews and analyzed using the Colaizzi method. Respondents first engaged in sexual intercourse between the ages of 16 and 20, with the most common age being 18 (43%). The primary reasons included feelings of love, the desire to strengthen relationships, and partner pressure. Other contributing factors included lack of family attention, emotional impulses, and curiosity. The main impact was psychological, manifesting as guilt, regret, anxiety, and fear of social stigma. However, some individuals who accepted their condition tended to cope better. Losing virginity has a significant psychological impact, particularly in the form of regret and social fear. Individuals with better self-acceptance tend to experience milder effects.